VD_FINDINFO Décision / 2023 / 496 vom 27. Juni 2023 - VD Tribunal cantonal (2023)
DEMANDE ADRESSÉE À L'AUTORITÉ, RÉCUSATION, POLICE, COMPÉTENCE, TRIBUNAL FÉDÉRAL | 380 CPP (CH), 56 CPP (CH), 59 CPP (CH), 91 al. 4 CPP (CH)